Complication Risk in Primary and Revision Minimally Invasive Lumbar Interbody Fusion: A Comparable Alternative to Conventional Open Techniques?. Issue 5 (August 2020) - Bortz, Cole; Alas, Haddy; Segreto, Frank; Horn, Samantha R.; Varlotta, Christopher; Brown, Avery E.; Pierce, Katherine E.; Ge, David H.; Vasquez-Montes, Dennis; Lafage, Virginie; Lafage, Renaud; Fischer, Charla R.; et al.
Study Design: Retrospective cohort study of prospective patients undergoing minimally invasive lumbar fusion at a single academic institution. Objective: To assess differences in perioperative outcomes between primary and revision MIS (minimally invasive surgical) lumbar interbody fusion patients and compare with those undergoing corresponding open procedures. Methods: Patients ≥18 years old undergoing lumbar interbody fusion were grouped by surgical technique: MIS or open. Patients within each group were propensity score matched for comorbidities and levels fused. Patient demographics, surgical factors, and perioperative complication incidences were compared between primary and revision cases using means comparison tests, as appropriate. Results: Of the 214 lumbar interbody fusion patients included after propensity score matching, 44 (21%) cases were MIS, and 170 (79%) were open. For MIS patients, there were no significant differences between primary and revision cases in estimated blood loss (EBL; 344 vs 299 cm 3, P = .682); however, primary cases had longer operative times (301 vs 246 minutes, P = .029). There were no differences in length of stay (LOS), intensive care unit LOS, readmission, and intraoperative or postoperative complications (all P > .05). For open patients, there were no differences between primary and revision cases in EBL ( P > .05), although revisions had longer operative times (331 vs 278 minutes, P = .018) and more postoperative complications (61.7% vs 23.8%, P < .001). MIS revision procedures were shorter than open revisions (182 vs 213 minutes, P = .197) with significantly less EBL (294 vs 965 cm 3, P < .001), shorter inpatient and intensive care unit LOS, and fewer postoperative complications (all P < .05). Conclusions: Clinical outcomes of revision MIS lumbar interbody fusion were similar to those of primary surgery. Additionally, MIS techniques were associated with less EBL, shorter LOS, and fewer perioperative complications than corresponding open revisions.